2002
DOI: 10.1210/en.2002-220420
|View full text |Cite
|
Sign up to set email alerts
|

The Increased Bone Mass in ΔFosB Transgenic Mice Is Independent of Circulating Leptin Levels

Abstract: Transgenic mice overexpressing deltaFosB, a naturally occurring splice variant of FosB, develop an osteosclerotic phenotype. The increased bone formation has been shown to be due, at least in part, to autonomous effects of deltaFosB isoforms on cells of the osteoblast lineage. However, abdominal fat and marrow adipocytes are also markedly decreased in deltaFosB mice, leading to low serum leptin levels. Increased bone mass has been linked to the absence of leptin and leptin receptor signaling in ob/ob and db/db… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 26 publications
4
24
0
Order By: Relevance
“…We had previously found, however, that marrow cells from the NSE-⌬FosB mice formed markedly fewer adipocytes in culture than did those from control animals (47). When bone marrow stromal cells from control, OG2-⌬FosB, and NSE-⌬FosB mice were cultured with ascorbic acid and ␤-glycerophosphate, the adipogenic capacity of bone marrow cultures from OG2-⌬FosB transgenic mice, shown by staining with Oil Red O, was comparable to that of cultures established from control mice, while adipocyte formation was dramatically reduced in cultures from NSE-⌬FosB transgenic mice, as reported previously (25,47) (Fig. 3C).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…We had previously found, however, that marrow cells from the NSE-⌬FosB mice formed markedly fewer adipocytes in culture than did those from control animals (47). When bone marrow stromal cells from control, OG2-⌬FosB, and NSE-⌬FosB mice were cultured with ascorbic acid and ␤-glycerophosphate, the adipogenic capacity of bone marrow cultures from OG2-⌬FosB transgenic mice, shown by staining with Oil Red O, was comparable to that of cultures established from control mice, while adipocyte formation was dramatically reduced in cultures from NSE-⌬FosB transgenic mice, as reported previously (25,47) (Fig. 3C).…”
Section: Resultssupporting
confidence: 83%
“…In vivo, an inverse relationship between the number of osteoblasts and bone marrow adipocytes has been demonstrated in several forms of osteopenia, where decreased bone mass is often associated with increased adipogenesis (6,29,57,60). Conversely, we have reported an osteosclerotic phenotype accompanied by decreased adipogenesis in transgenic mice that overexpress the AP-1 transcription factor ⌬FosB under the control of the NSE promoter (25,47,53).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…As expected from reduced fat storage, Fra1tg mice show a reduced level of circulating leptin that might contribute to increased bone formation by osteoblasts (Ducy et al, 2000). However, this decreased level of leptin was not sufficient to affect the food intake of the Fra1tg mice, and although the role of leptin in regulating bone mass can be dissociated from its function in regulating appetite (Shi et al, 2008), leptin was not found to have a role in the very similar bone phenotype that developed in DfosB transgenic mice (Kveiborg et al, 2002). Osteocalcin was recently characterized as a hormone that regulates insulin production by increasing -cell proliferation (Lee et al, 2007).…”
Section: Discussionmentioning
confidence: 93%
“…In mice loss-and gain-of-function mutations of Fos and ATF members, and to a lesser extent of Jun members, demonstrate that these factors are important for osteoblast differentiation and function (Wagner and Eferl, 2005). Whereas Fra-1 (Fos-related antigen 1, Fosl1) and DFosB (the short isoform of FosB) promote osteoblast differentiation and activity Kveiborg et al, 2002;Lefterova and Lazar, 2009;Zhao et al, 2008), Fra-2 (Fosrelated antigen 2, Fosl2) is important in normal physiology and disease, such as in pulmonary fibrosis . Fra-2 also regulates chondrocyte differentiation and bone remodeling by controlling osteoclast size and activity (Bozec et al, 2008).…”
Section: Introductionmentioning
confidence: 99%